Evaluation Of Information Technology Governance at Mikroskil University Using COBIT 2019 Framework with BAI11 Domain - Anugrahi Bawani Sipayung; Roni Yunis; Elly . (International Journal of Research and Applied Technology (INJURATECH), 2022)
IT governance evaluation can help organizations to improve the quality of IT services, reduce risks, maximize IT performance and achieve their goals effectively. Mikroskil University is one of the universities that utilize the use of IT in supporting its business processes. Mikroskil University has an IT unit/department that is responsible for IT management and IT governance as well as dealing with IT/IS-related issues, namely the Information System and Digital Transformation (SITD). Based on the initial study conducted, several problems arise in higher education IT governance, so it is necessary to carry out an evaluation. This evaluation uses the COBIT 2019 framework because it is more flexible and there are design factors that can make it easier to get process objectives that will be evaluated as the main focus of the organization. This framework makes it easier for researchers to evaluate processes in universities. The domain that becomes the objective of IT governance in this research is BAI11 (Managed projects). The results of this study indicate that the capability level of Mikroskil University is at level 1 (performed). Meanwhile, the maturity level is at level 2 (managed). Based on the results of the capability and maturity level values, a gap value will be sought to be used as a basis for making recommendations for improvement. The results of this study provide recommendations for improvement to achieve the expected targets of higher education. Mikroskil University's capability level is at level 1 (performed). Meanwhile, the maturity level is at level 2 (managed). Based on the results of the capability and maturity level values, a gap value will be sought to be used as a basis for making recommendations for improvement. The results of this study provide recommendations for improvement to achieve the expected targets of higher education. Mikroskil University's capability level is at level 1 (performed). Meanwhile, the maturity level is at level 2 (managed). Based on the results of the capability and maturity level values, a gap value will be sought to be used as a basis for making recommendations for improvement. The results of this study provide recommendations for improvement to achieve the expected targets of higher education.